2021
DOI: 10.2196/25288
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology Use in Suicide Prevention: Scoping Review

Abstract: Background The use of information and communication technology (ICT) in suicide prevention has progressed rapidly over the past decade. ICT plays a major role in suicide prevention, but research on best and promising practices has been slow. Objective This paper aims to explore the existing literature on ICT use in suicide prevention to answer the following question: what are the best and most promising ICT practices for suicide prevention? … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 134 publications
0
20
0
Order By: Relevance
“… 13 14 For example, there are 38 mental health apps available from the Google Play Store (Android) and Apple App Store, and 11 of them are comprised of in-app crisis resources such as safety planning intervention (SPI). 15 Rassy and colleagues 14 have shown that ICTs for suicide prevention can provide an interactive, personalised and accessible way to reach various populations to identify and provide care to the individuals at risk. 14 Although more additional higher quality, randomised controlled studies are required, evidence to date shows promising outcomes of the ICT-based interventions for suicide prevention, including high acceptability from the patients and some beneficial effects on suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 14 For example, there are 38 mental health apps available from the Google Play Store (Android) and Apple App Store, and 11 of them are comprised of in-app crisis resources such as safety planning intervention (SPI). 15 Rassy and colleagues 14 have shown that ICTs for suicide prevention can provide an interactive, personalised and accessible way to reach various populations to identify and provide care to the individuals at risk. 14 Although more additional higher quality, randomised controlled studies are required, evidence to date shows promising outcomes of the ICT-based interventions for suicide prevention, including high acceptability from the patients and some beneficial effects on suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Rassy and colleagues 14 have shown that ICTs for suicide prevention can provide an interactive, personalised and accessible way to reach various populations to identify and provide care to the individuals at risk. 14 Although more additional higher quality, randomised controlled studies are required, evidence to date shows promising outcomes of the ICT-based interventions for suicide prevention, including high acceptability from the patients and some beneficial effects on suicidal ideation. 16 In clinical settings, on the other hand, it remains unknown which ICT-based interventions for suicide prevention have been implemented and are being delivered by clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…There is a surplus of ICT-based interventions for mental health care, including suicide prevention. 13,14 For example, there are 38 mental health apps available from the Google Play Store (Android) and Apple App Store, and 11 of them are comprised of in-app crisis resources such as safety planning intervention (SPI). 15 Rassy and colleagues 14 have shown that ICTs for suicide prevention can provide an interactive, personalized, and accessible way to reach various populations to identify and provide care to the individuals at risk.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 For example, there are 38 mental health apps available from the Google Play Store (Android) and Apple App Store, and 11 of them are comprised of in-app crisis resources such as safety planning intervention (SPI). 15 Rassy and colleagues 14 have shown that ICTs for suicide prevention can provide an interactive, personalized, and accessible way to reach various populations to identify and provide care to the individuals at risk. 14 Although more additional higher quality, randomized controlled studies are required, evidence to date shows promising outcomes of the ICTbased interventions for suicide prevention, including high acceptability from the patients and some beneficial effects on suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation